2019
DOI: 10.3390/ijerph16152732
|View full text |Cite
|
Sign up to set email alerts
|

Progress Evaluation for Transnational Restaurant Chains to Reformulate Products and Standardize Portions to Meet Healthy Dietary Guidelines and Reduce Obesity and Non-Communicable Disease Risks, 2000–2018: A Scoping and Systematic Review to Inform Policy

Abstract: Transnational restaurant chains sell food and beverage products in 75 to 139 countries worldwide linked to obesity and non-communicable diseases (NCDs). This study examined whether transnational restaurant chains reformulated products and standardized portions aligned with healthy dietary guidelines and criteria. Firstly, we describe the transnational restaurant industry structure and eating trends. Secondly, we summarize results from a scoping review of healthy dietary guidelines for restaurants. Thirdly, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 95 publications
0
11
0
Order By: Relevance
“…For instance, Cetthakrikul et al [44] reported food companies in Thailand lacked sufficient specificity and often did not provide detailed criteria in food marketing to children, nutrition and health claims, and food accessibility. A review of commitments and disclosures of companies in 30 countries [33] also revealed wide variations in country specific policies of transnational chain restaurants regarding improving healthfulness of their menus, as well as time commitments to executing these targets. Lack of disclosures and uncertain application of global commitments within Malaysia were identified as issues for most of the global and regional companies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Cetthakrikul et al [44] reported food companies in Thailand lacked sufficient specificity and often did not provide detailed criteria in food marketing to children, nutrition and health claims, and food accessibility. A review of commitments and disclosures of companies in 30 countries [33] also revealed wide variations in country specific policies of transnational chain restaurants regarding improving healthfulness of their menus, as well as time commitments to executing these targets. Lack of disclosures and uncertain application of global commitments within Malaysia were identified as issues for most of the global and regional companies.…”
Section: Discussionmentioning
confidence: 99%
“…The BIA-Obesity tool has previously been applied to Australia [28][29][30], New Zealand [31], and Canada [32]. It has been recommended that BIA-Obesity country level evaluations be used to monitor and evaluate food industry's progress towards meeting country specific nutrition policies and health criteria, while at the same time building a central database to enable cross-country comparisons [27,33].…”
Section: Introductionmentioning
confidence: 99%
“…Recommendations by public health practitioners have been issued to downsize and standardize portions to 600-700 calories or 2510-2930 kilojoules/meal as an important strategy for restaurants to help costumers reduce obesity and NCD risks. However, this research found a lack of clear, universal, and internationally accepted standards for transnational restaurant chains to adopt portion or serving sizes for meals, beverages, side dishes, and desserts served to children, adolescents and adults [21]. The studies reviewed (n = 50) also revealed wide variation within and across countries, regions, firms, and restaurant chains to reduce energy, saturated fats, trans fats, sodium, and standardized portions.…”
Section: Introductionmentioning
confidence: 94%
“…The restaurant business sector, which includes QSRs, FCRs, and full-service restaurant (FSR) chains and independent restaurants, has the resources and capacity to reformulate menu items or introduce new items [19][20][21]. United States (US) chain restaurant establishments have demonstrated progress to improve the nutrition composition of items and reduce meal size or portions served to meet recommended nutrient targets of public health experts, namely, the United States Department of Agriculture and the Dietary Guidelines for Americans [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation